Integral boundary-value problem for impulsive fractional functional differential equations with infinite delay - Archana Chauhan; Jaydev Dabas; Mukesh Kumar (Electronic Journal of Differential Equations, 2012)
In this article, we establish a general framework for finding solutions for impulsive fractional integral boundary-value problems. Then, we prove the existence and uniqueness of solutions by applying well known fixed point theorems. The obtained results are illustrated with an example for their feasibility.